The impact of market risk exposure on banks' financial performance: evidence from the MENA region / Amer N. Bani Yousef ... [et al.] - Bani Yousef, Amer N.; Taha, Roshaiza; Muhmad, Siti Nurain; Zainul Abidin, Ahmad Firdhauz (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study investigated the relationship between market risk and bank financial performance in 14 Middle East and North African (MENA) countries, employing quantile regression estimations. The data of 135 banks in the MENA region from 2015 to 2019 were collected from the Bankscope and World Bank. The OLS results showed that market risk was positively associated with bank performance. Quartile regression also indicated that only banks in the median and 90% quartiles had a positive association between market risk and performance. This proved that MENA banks have high performance when exposed to high market risk, in line with the perspectives of risk-return trade-off views. This implies that banks are risk-takers in conducting business in the highly competitive market in the MENA region. Banks tend to provide various financial services, which can secure generating returns. Besides, the findings also provide insight into banks' preference in utilizing leverage to generate profits. The findings provide a cogent argument to the bankers and regulators in MENA region on the role and impact of market risk towards banks financial stability.